Presence of queuine in Drosophila melanogaster: correlation of free pool with queuosine content of tRNA and effect of mutations in pteridine metabolism. - Jacobson, K B (1981)
Queuine, a modified form of 7-deazaguanine present in certain transfer RNAs, is shown to occur in Drosophila melanogaster adults in a free form and its concentration varies as a function of age, nutrition and genotype. In several, but not all mutant strains, the concentrations of queuine and the Q(+) (queuine-containing) form of tRNATyr are correlated. The bioassay employs L-M cells which respond to the presence of queuine by an increase in their Q(+)tRNAAsp that is accompanied by a decrease in the Q(-)tRNAAsp isoacceptors. The increase in Q(+)tRNATyr in Drosophila that occurs on a yeast diet is accompanied by an increase in queuine. Similarly the increase of Q(+)tRNAs with age also is accompanied by an increase in free queuine. In two mutants, brown and sepia, these correlations were either diminished or failed to occur. Indeed, the extract of both mutants inhibited the response of the L-M cells to authentic queuine. When the pteridines that occur at abnormally high levels in sepia were used at 1 x 10(-6)M, the inhibition of the L-M cell assay occurred in the order biopterin greater than pterin greater than sepiapterin. These pteridines were also inhibitory for the purified guanine:tRNA transglycosylase from rabbit but the relative effectiveness then was pterin greater than biopterin greater than sepiapterin. Pterin was competitive with guanine in the enzyme reaction with Ki = 0.9 x 10(-7)M. Also when an extract of sepia was chromatographed on Sephadex G-50, the pteridine-containing fractions only were inhibitory toward the L-M cell assay or the enzyme assay. These results indicate that free queuine occurs in Drosophila but also that certain pteridines may interfere with the incorporation of queuine into RNA.